Cardiac function evaluation in healthy volunteers and patients with implantable cardioverter-defibrillators using high-bandwidth spoiled gradient-echo cine - Calder D. Sheagren; Naseem Shadafny; Terenz Escartin; Maria Terricabras; Christopher C. Cheung; Idan Roifman; Graham A. Wright (Journal of Cardiovascular Magnetic Resonance)
Background: Implantable cardioverter-defibrillators (ICDs) cause banding artifacts around areas of B0 inhomogeneity in conventional steady-state free precession (SSFP) cine sequences. Alternatively, high-bandwidth gradient-recalled echo (GRE) cine sequences can be used to minimize artifacts in the myocardium. In this study, we assessed the bias and interobserver variability in cardiac volumes and ejection fractions between GRE cines in acquired in the presence of ICDS and ground-truth SSFP cines (without ICDs present) in a population of healthy volunteers. Further, a small cohort of ICD patients was recruited and scanned to demonstrate clinical feasibility. Methods: High-bandwidth GRE cine was performed in 11 healthy volunteers with taped ICDs mimicking clinical implants. After the ICD was removed, ground-truth SSFP cine was performed. Two observers separately assessed image quality metrics and contoured the cine images to return cardiac volumes and ejection fractions. Nine patients with an ICD were also scanned with the GRE cine protocol before contrast administration; data were contoured by two observers and analyzed for interobserver agreement. Results: In the healthy volunteer dataset, no statistically significant differences were found when comparing volumes or ejection fractions between sequences (p > 0.05). Statistically significant differences were found when comparing right ventricular ejection fraction (RVEF) (p = 0.009) and right ventricular end-systolic volume (p = 0.029) between observers, with no other significant interobserver differences. The interobserver variability of patient left ventricular ejection fraction and RVEF data was 3–4%, with lower image quality metrics for patient scans than volunteer scans. Conclusion: GRE cine imaging in healthy volunteers with taped ICDs demonstrated good agreement with SSFP cine, but increased interobserver variability. In patients, reducing the breath-hold duration caused a decrease in image quality, with GRE cine imaging in patients with ICDs demonstrating poorer image quality and greater interobserver variability than in healthy volunteer studies. Future work is needed to improve GRE cine image quality in patients with ICDs to reduce interobserver variability and improve clinical confidence.